1975
DOI: 10.7326/0003-4819-83-3-330
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Calcification in Chronic Dialysis Patients

Abstract: A prospective study of 31 chronically hemodialyzed patients was made to investigate the incidence and pathology of pulmonary calcification and the relation of the latter to ventilatory function. Fifteen of the patients have died thus far; 9 had evidence of lung calcification. The lesions occurred predominately in alveolar septa and were associated with varying degrees of fibrosis and alveolar septal thickening. Only one patient had X-ray evidence of calcification. An X-ray diffraction analysis showed a predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
148
0
2

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(151 citation statements)
references
References 15 publications
1
148
0
2
Order By: Relevance
“…18 -21 In patients with uremia, whitlockite has been described as a preliminary stage in soft tissue calcifications but not in vascular calcifications. 8,22,23 Most studies so far have exclusively detected hydroxyapatite or carbonated apatite in uremic vascular calcifications 7,8 -except for one study, which reported brushite in arteriovenous fistulas. 9 Whitlockite has been described only once as a chemical compound in the nonuremic human aorta 24 ; however, in this context, it has to be mentioned that hydroxyapatite rarely exists in its pure form in biologic systems but occurs often as carbonated apatite, which may also contain magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…18 -21 In patients with uremia, whitlockite has been described as a preliminary stage in soft tissue calcifications but not in vascular calcifications. 8,22,23 Most studies so far have exclusively detected hydroxyapatite or carbonated apatite in uremic vascular calcifications 7,8 -except for one study, which reported brushite in arteriovenous fistulas. 9 Whitlockite has been described only once as a chemical compound in the nonuremic human aorta 24 ; however, in this context, it has to be mentioned that hydroxyapatite rarely exists in its pure form in biologic systems but occurs often as carbonated apatite, which may also contain magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic pulmonary calcifications have been shown to be present in 60-80% of autopsied haemodialysis patients, although rarely recognized during life [6], their extent is usually reflected in the survival of the patient Although many patients remain asymptomatic, some develop severe respiratory symptoms which are related to the extent of calcification. Restrictive lung diseases with progressive decrease in TL,CO, VC and hypoxaemia may be associated with rising levels of pulmonary calcium levels [3].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis has been in clinical use years (36), but some of its diverse and u complications have only recently becom (37,38). The acute leukopenia of hemod described 8 yr ago (1, 2), but its mechani mained obscure (39).…”
Section: Discussionmentioning
confidence: 99%